FDG-PET scan in colorectal cancer - (:unkn) unknown (AKAD DOKTORLAR YAYINEVI, 2008)
[18F] Fluorodeoxyglucose (FDG) positron emission tomography (PET) is a useful imaging tool in the management of patients with colorectal carcinoma. This technique has an essential role in the staging of patients prior to surgical resection of recurrence and metastases, in the localization of recurrence in patients with an unexplained rise in serum carcinoembryonic antigen, in the assessment of residual masses after treatment, in determining tumor response to therapy in neo-adjuvant settings, and in evaluating colorectal cancer prognosis. It is possible to measure and visualize metabolic changes in cancer cells via FDG-PET. Combined PET/CT scans permit exact localization with anatomical criteria of the hypermetabolic FDG avid malignant lesions. This review aims to outline the current and future role of FDG-PET in the field of colorectal cancer.
Keywords: FDG; PET/CT; colorectal cancer; POSITRON-EMISSION-TOMOGRAPHY; CARCINOEMBRYONIC ANTIGEN; LIVER METASTASES; RADIOFREQUENCY ABLATION; F-18-FDG PET; COLON; RECURRENCE; IMPACT; RESECTION; THERAPY